Rare cancers are not rare in Asia as well: The rare cancer burden in East Asia. (August 2020) - Matsuda, Tomohiro; Won, Young-Joo; Chun-ju Chiang, RuRu; Lim, Jiwon; Saika, Kumiko; Fukui, Keisuke; Lee, Wen-Chung; Botta, Laura; Bernasconi, Alice; Trama, Annalisa
Highlights: Proportions of rare in overall incidence were around 16–24% in the 3 Asia and in EU. Most rare cancers in Europe were also rare in the Asian countries considered. Observed differences were due to well-known risk factors. Abstract: Introduction: Epidemiologic information on rare cancers is scarce outside of the Western countries. The project "surveillance of rare cancers in Asia" (RARECAREnet Asia) provides, for the first time, the burden of rare cancers in some Asian countries based on the latest list. Objectives: 1) to assess whether the European list of rare cancers fits the Asian setting and 2) to compare the incidences of rare cancers between Europe and Asian countries. Material and methods: Population-based cancer registry data on patients diagnosed from 2011 to 2015 in Japan, Korea, and Taiwan and patients diagnosed from 2000 to 2007 in 94 European registries were analysed. The incidences for all cancers were calculated; they were then grouped into several tiers and families according to the rare cancer list, and whether cancers rare was examined. Results: Rare cancer counts according to the list in the observed population were 196 in Japan, 203 in Korea, 198 in Taiwan, and 198 in the EU. The proportions of rare in overall incidence were 16.3% in Japan, 23.7% in Korea, 24.2% in Taiwan, and 22.2% in the EU. The numbers of newly diagnosed rare cancer cases in 2015 were 140, 188 in Japan, 52, 071 in Korea, and 24, 147 in Taiwan. Conclusion: Most rare cancers in Europe were also rare in the Asian countries considered. The observed differences were due to well-known risk factors. The European definition and list of rare cancers appear to reflect well cancer incidence in East Asia.